Do patients with basilar or vertebral artery stenosis have a higher stroke incidence poststenting?. (4th December 2009) - Jiang, W-J; Du, B; Hon, S F K; Jin, M; Xu, X-T; Ma, N; Gao, F; Dong, K-H
Abstract : Background and aim: Posterior circulation stenosis may be a risk factor associated with stroke after intracranial stenting as compared with anterior circulation stenosis. Our aim was to test our hypothesis that there was no difference in clinical outcome poststenting between patients with severe stenosis of the basilar artery (BA) and intracranial vertebral artery (VA). Methods: Using the Cox proportional hazards regression model adjusted for prespecified factors (qualifying event, and timing of stenting after the qualifying event), we compared primary endpoint (ischemic stroke in the vertebrobasilar territory, including any stroke or death within 30 days of stenting) between patients with severe symptomatic atherosclerotic BA and VA stenosis who underwent elective stenting in our prospective database. Analysis was by intention-to-treat principle. Results: Primary endpoint event occurred in 13 (18.8%) of 69 patients with BA stenosis during a mean 23.4 months (9 within 30 days and 4 afterward) and 3 (4.3%) of 70 patients with VA stenosis during a mean 26.4 months (2 within 30 days and 1 afterward). Patients with BA stenosis had a significantly higher risk of the primary endpoint (adjusted HR=4.87, 95% CI 1.37 to 17.29; p=0.014) or any stroke or death within 30 days of stenting (adjusted HR=5.13, 95% CI 1.10 to 23.96; p=0.038) than those with VA stenosis. Conclusion: A significantly higher stroke risk poststenting exists in patients with severe BA stenosis than those with VA stenosis. The discrepancy in clinical outcome after stenting between patients with BA and VA stenosis should be considered in clinical practice and stenting trials.